PENGENDALIAN SUHU DALAM RUANG BERBASIS LOGIKA FUZZY DENGAN MENGGUNAKAN NATIONAL INSTRUMENT MYRIO 1900 - Bustanul Arifin; Agus Adhi Nugroho (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
The design of room temperature control using conventional technology such as PID are not simple since using complex mathematics calculation. The fuzzy logic control implemented as a temperature control need a simple design and calculation. The temperatur sensor PmodTMP3 equipped with Infrared sensor to detect the amount of people to get appropriate speed of evaporator motor in order to meet the temperature setting. My RIO 1900 with LabView 2015 use as controller.  The  DC  motor  start  to  rotate  when  sensor  counted  35  people entering the room (2,6 volt). And when 40 people entering the room, the voltage rise to 5 volt. This prove that fuzzy logic control working appropriate. Keywords: temperature control, fuzzy logic, myRIO1900